Transcriptome profiling of monocytes from XLA patients revealed the innate immune function dysregulation due to the BTK gene expression deficiency - Hoda Mirsafian; Adiratna Mat Ripen; Wai-Mun Leong; Chai Teng Chear; Saharuddin Bin Mohamad; Amir Feisal Merican (Scientific Reports, 2017)
Abstract X-linked agammaglobulinemia (XLA) is a rare genetic disorder, caused by mutations in BTK (Bruton’s Tyrosine Kinase) gene. Deep high-throughput RNA sequencing (RNA-Seq) approach was utilized to explore the possible differences in transcriptome profiles of primary monocytes in XLA patients compared with healthy subjects. Our analysis revealed the differences in expression of 1,827 protein-coding genes, 95 annotated long non-coding RNAs (lncRNAs) and 20 novel lincRNAs between XLA patients and healthy subjects. GO and KEGG pathway analysis of differentially expressed (DE) protein-coding genes showed downregulation of several innate immune-related genes and upregulation of oxidative phosphorylation and apoptosis-related genes in XLA patients compared to the healthy subjects. Moreover, the functional prediction analysis of DE lncRNAs revealed their potential role in regulating the monocytes cell cycle and apoptosis in XLA patients. Our results suggested that BTK mutations may contribute to the dysregulation of innate immune system and increase susceptibility to apoptosis in monocytes of XLA patients. This study provides significant finding on the regulation of BTK gene in monocytes and the potential for development of innovative biomarkers and therapeutic monitoring strategies to increase the quality of life in XLA patients.